Late neurological consequences of SARS-CoV-2 infection: New challenges for the neurologist - Korchut, Agnieszka; Rejdak, Konrad (Frontiers in Neuroscience, 2023)
Objective In this study, a systematic review of the literature was performed to study the frequency of neurological symptoms and diseases in adult patients with COVID-19 that may be late consequences of SARS-CoV-2 infection. Methods Relevant studies were identified through electronic explorations of Scopus, PubMed, and Google Scholar. We followed PRISMA guidelines. Data were collected from studies where the diagnosis of COVID-19 was confirmed and its late neurological consequences occurred at least 4 weeks after initial SARS-CoV-2 infection. Review articles were excluded from the study. Neurological manifestations were stratified based on frequency (above 5, 10, and 20%), where the number of studies and sample size were significant. Results A total of 497 articles were identified for eligible content. This article provides relevant information from 45 studies involving 9,746 patients. Fatigue, cognitive problems, and smell and taste dysfunctions were the most frequently reported long-term neurological symptoms in patients with COVID-19. Other common neurological issues were paresthesia, headache, and dizziness. Conclusion On a global scale of patients affected with COVID-19, prolonged neurological problems have become increasingly recognized and concerning. Our review might be an additional source of knowledge about potential long-term neurological impacts.